CD147 Expressed on Memory CD4+ T Cells Limits Th17 Responses in Patients With Rheumatoid Arthritis - Miao, Jinlin; Zhang, Kui; Zheng, Zhaohui; Zhang, Rui; Lv, Minghua; Guo, Na; Xu, Yingming; Han, Qing; Chen, Zhinan; Zhu, Ping (Frontiers in Immunology, 2020)
Rheumatoid arthritis (RA) is a common autoimmune disease in which T helper-type 17 (Th17) cells have been critically involved. CD147 is a T cell activation-associated molecule and is involved in T cell development. However, it remains unclear whether CD147 participates in Th17 responses in RA patients. In this study, we demonstrated that in both the RA and healthy controls (HC) groups, CD147 expression on CD4+ T cells was increased in CCR6+ and CD161+ subsets, and was associated with IL-17 production. Ligation of CD147 with its monoclonal antibody (mAb) strongly inhibited Th17 responses, and knock down of CD147 expression on CD4+ Tm cells specifically enhanced Th17 responses, triggered by coculture with in vitro activated monocytes from HC. Further functional studies showed that anti-CD147 mAb decreased the activation of AKT, mTORC1 and STAT3 signaling, which is known to enhance Th17 responses. Ligation of CD147 with its mAb on CD4+ Tm cells specifically reduced Th17 responses induced by in vitro or in vivo activated monocytes from RA patients. In collagen-induced arthritis model, anti-CD147 mAb treatment reduced the Th17 levels and severity of arthritis in vivo. These data suggest that CD147 plays a negative role in regulating human Th17 responses. Anti-CD147 mAb can limit the extraordinary proliferation of Th17 cells and may be a new therapeutic option in RA.